Effect Of Temperature And NaCl Concentration On Synthesis Of Silver Nanoparticles Prepared In Aqueous Medium - Nurul Akma, Reduan; Suriati, Ghazali; Saidatul Shima, Jamari (Asian Research Publishing Network (ARPN), 2016)
Unique optical and physical behaviour of nanoparticles compared to corresponding bulk materials has gain considerably interest and the research in synthesizing and application of nanoparticles has expanded rapidly over a last decade. This present study reported on the well-dispersity synthesis of nano-size material via chemical reduction of silver nitrate (AgNO3) by sodium borohydride (NaBH4) in an aqueous medium. In this study, there are two parameters that were manipulated which are temperatures; varied from 25 °C until 90 °C and concentration of sodium chloride (NaCl) that was varied from 0.0mM to 30.0 mM respectively. The UV-Vis analysis of silver nanoparticles shows maximum peak were determined at the range of 404nm- 410 nm which is the characteristic of Ag particles. Meanwhile, the morphology of assynthesized silver nanoparticles (AgNPs) that investigated by using Field Emission Scanning Electron Microscopy (FESEM) reveals a spherical particles size with the size range of 20 nm-160 nm. Analysis of AgNPs diameter by using Image J reveal that the smallest nano-size AgNPs is at 3.0 mM NaCl and at temperature 45°C which is ~50 nm.